The Mutational Landscape of Acute Promyelocytic Leukemia Reveals an Interacting Network of Co-Occurrences and Recurrent Mutations. - Ibáñez, Mariam; Carbonell-Caballero, José; García-Alonso, Luz; Such, Esperanza; Jiménez-Almazán, Jorge; Vidal, Enrique; Barragán, Eva; López-Pavía, María; LLop, Marta; Martín, Iván; Gómez-Seguí, Inés; Montesinos, Pau; et al. (PLoS One, 2016)
Preliminary Acute Promyelocytic Leukemia (APL) whole exome sequencing (WES) studies have identified a huge number of somatic mutations affecting more than a hundred different genes mainly in a non-recurrent manner, suggesting that APL is a heterogeneous disease with secondary relevant changes not yet defined. To extend our knowledge of subtle genetic alterations involved in APL that might cooperate with PML/RARA in the leukemogenic process, we performed a comprehensive analysis of somatic mutations in APL combining WES with sequencing of a custom panel of targeted genes by next-generation sequencing. To select a reduced subset of high confidence candidate driver genes, further in silico analysis were carried out. After prioritization and network analysis we found recurrent deleterious mutations in 8 individual genes (STAG2, U2AF1, SMC1A, USP9X, IKZF1, LYN, MYCBP2 and PTPN11) with a strong potential of being involved in APL pathogenesis. Our network analysis of multiple mutations provides a reliable approach to prioritize genes for additional analysis, improving our knowledge of the leukemogenesis interactome. Additionally, we have defined a functional module in the interactome of APL. The hypothesis is that the number, or the specific combinations, of mutations harbored in each patient might not be as important as the disturbance caused in biological key functions, triggered by several not necessarily recurrent mutations.
Keywords: Exome; Gene Regulatory Networks; Genome, Human; Humans; INDEL Mutation; Leukemia, Promyelocytic, Acute; mutation; Mutation Rate; Polymorphism, Single Nucleotide; Reproducibility of Results

Whole exome sequencing of Rett syndrome-like patients reveals the mutational diversity of the clinical phenotype. - Lucariello, Mario; Vidal, Enrique; Vidal, Silvia; Saez, Mauricio; Roa, Laura; Huertas, Dori; Pineda, Mercè; Dalfó, Esther; Dopazo, Joaquin; Jurado, Paola; Armstrong, Judith; Esteller, Manel (Hum Genet, 2016)
Classical Rett syndrome (RTT) is a neurodevelopmental disorder where most of cases carry MECP2 mutations. Atypical RTT variants involve mutations in CDKL5 and FOXG1. However, a subset of RTT patients remains that do not carry any mutation in the described genes. Whole exome sequencing was carried out in a cohort of 21 female probands with clinical features overlapping with those of RTT, but without mutations in the customarily studied genes. Candidates were functionally validated by assessing the appearance of a neurological phenotype in Caenorhabditis elegans upon disruption of the corresponding ortholog gene. We detected pathogenic variants that accounted for the RTT-like phenotype in 14 (66.6 %) patients. Five patients were carriers of mutations in genes already known to be associated with other syndromic neurodevelopmental disorders. We determined that the other patients harbored mutations in genes that have not previously been linked to RTT or other neurodevelopmental syndromes, such as the ankyrin repeat containing protein ANKRD31 or the neuronal acetylcholine receptor subunit alpha-5 (CHRNA5). Furthermore, worm assays demonstrated that mutations in the studied candidate genes caused locomotion defects. Our findings indicate that mutations in a variety of genes contribute to the development of RTT-like phenotypes.
Keywords: Adolescent; Adult; Animals; Caenorhabditis elegans; Carrier Proteins; Cell Cycle Proteins; Child; Child, Preschool; DNA Mutational Analysis; Exome; Female; Forkhead Transcription Factors; Genetic Variation; High-Throughput Nucleotide Sequencing; Humans; Methyl-CpG-Binding Protein 2; mutation; Nerve Tissue Proteins; Protein Serine-Threonine Kinases; Receptors, Nicotinic; Rett Syndrome

Using activation status of signaling pathways as mechanism-based biomarkers to predict drug sensitivity. - Amadoz, Alicia; Sebastián-Leon, Patricia; Vidal, Enrique; Salavert, Francisco; Dopazo, Joaquin (Sci Rep, 2015)
Many complex traits, as drug response, are associated with changes in biological pathways rather than being caused by single gene alterations. Here, a predictive framework is presented in which gene expression data are recoded into activity statuses of signal transduction circuits (sub-pathways within signaling pathways that connect receptor proteins to final effector proteins that trigger cell actions). Such activity values are used as features by a prediction algorithm which can efficiently predict a continuous variable such as the IC50 value. The main advantage of this prediction method is that the features selected by the predictor, the signaling circuits, are themselves rich-informative, mechanism-based biomarkers which provide insight into or drug molecular mechanisms of action (MoA).
Keywords: Algorithms; Antineoplastic Agents; biomarkers; Cell Line, Tumor; Cell Survival; gene expression; Humans; Lethal Dose 50; Neoplasms; Phosphorylation; Proteins; Signal Transduction

Exome sequencing identifies a new mutation in SERAC1 in a patient with 3-methylglutaconic aciduria. - Tort, Frederic; García-Silva, María Teresa; Ferrer-Cortès, Xènia; Navarro-Sastre, Aleix; Garcia-Villoria, Judith; Coll, Maria Josep; Vidal, Enrique; Jiménez-Almazán, Jorge; Dopazo, Joaquin; Briones, Paz; Elpeleg, Orly; Ribes, Antonia (Mol Genet Metab, 2013)
3-Methylglutaconic aciduria (3-MGA-uria) is a heterogeneous group of syndromes characterized by an increased excretion of 3-methylglutaconic and 3-methylglutaric acids. Five types of 3-MGA-uria (I to V) with different clinical presentations have been described. Causative mutations in TAZ, OPA3, DNAJC19, ATP12, ATP5E, and TMEM70 have been identified. After excluding the known genetic causes of 3-MGA-uria we used exome sequencing to investigate a patient with Leigh syndrome and 3-MGA-uria. We identified a homozygous variant in SERAC1 (c.202C>T; p.Arg68*), that generates a premature stop codon at position 68 of SERAC1 protein. Western blot analysis in patient's fibroblasts showed a complete absence of SERAC1 that was consistent with the prediction of a truncated protein and supports the pathogenic role of the mutation. During the course of this project a parallel study identified mutations in SERAC1 as the genetic cause of the disease in 15 patients with MEGDEL syndrome, which was compatible with the clinical and biochemical phenotypes of the patient described here. In addition, our patient developed microcephaly and optic atrophy, two features not previously reported in MEGDEL syndrome. We highlight the usefulness of exome sequencing to reveal the genetic bases of human rare diseases even if only one affected individual is available.
Keywords: Adolescent; Adult; Carboxylic Ester Hydrolases; Child; Exome; Female; High-Throughput Nucleotide Sequencing; Humans; Infant; Male; Metabolism, Inborn Errors; mutation

Discovering the hidden sub-network component in a ranked list of genes or proteins derived from genomic experiments. - García-Alonso, Luz; Alonso, Roberto; Vidal, Enrique; Amadoz, Alicia; De Maria, Alejandro; Minguez, Pablo; Medina, Ignacio; Dopazo, Joaquin (Nucleic Acids Res, 2012)
Genomic experiments (e.g. differential gene expression, single-nucleotide polymorphism association) typically produce ranked list of genes. We present a simple but powerful approach which uses protein-protein interaction data to detect sub-networks within such ranked lists of genes or proteins. We performed an exhaustive study of network parameters that allowed us concluding that the average number of components and the average number of nodes per component are the parameters that best discriminate between real and random networks. A novel aspect that increases the efficiency of this strategy in finding sub-networks is that, in addition to direct connections, also connections mediated by intermediate nodes are considered to build up the sub-networks. The possibility of using of such intermediate nodes makes this approach more robust to noise. It also overcomes some limitations intrinsic to experimental designs based on differential expression, in which some nodes are invariant across conditions. The proposed approach can also be used for candidate disease-gene prioritization. Here, we demonstrate the usefulness of the approach by means of several case examples that include a differential expression analysis in Fanconi Anemia, a genome-wide association study of bipolar disorder and a genome-scale study of essentiality in cancer genes. An efficient and easy-to-use web interface (available at http://www.babelomics.org) based on HTML5 technologies is also provided to run the algorithm and represent the network.
Keywords: Bipolar Disorder; Fanconi Anemia; Gene Regulatory Networks; Genes, Neoplasm; Genome-Wide Association Study; Genomics; Humans; Protein Interaction Mapping

Whole-genome bisulfite DNA sequencing of a DNMT3B mutant patient. - Heyn, Holger; Vidal, Enrique; Sayols, Sergi; Sanchez-Mut, Jose V; Moran, Sebastian; Medina, Ignacio; Sandoval, Juan; Simó-Riudalbas, Laia; Szczesna, Karolina; Huertas, Dori; Gatto, Sole; Matarazzo, Maria R; et al. (Epigenetics, 2012)
The immunodeficiency, centromere instability and facial anomalies (ICF) syndrome is associated to mutations of the DNA methyl-transferase DNMT3B, resulting in a reduction of enzyme activity. Aberrant expression of immune system genes and hypomethylation of pericentromeric regions accompanied by chromosomal instability were determined as alterations driving the disease phenotype. However, so far only technologies capable to analyze single loci were applied to determine epigenetic alterations in ICF patients. In the current study, we performed whole-genome bisulphite sequencing to assess alteration in DNA methylation at base pair resolution. Genome-wide we detected a decrease of methylation level of 42%, with the most profound changes occurring in inactive heterochromatic regions, satellite repeats and transposons. Interestingly, transcriptional active loci and ribosomal RNA repeats escaped global hypomethylation. Despite a genome-wide loss of DNA methylation the epigenetic landscape and crucial regulatory structures were conserved. Remarkably, we revealed a mislocated activity of mutant DNMT3B to H3K4me1 loci resulting in hypermethylation of active promoters. Functionally, we could associate alterations in promoter methylation with the ICF syndrome immunodeficient phenotype by detecting changes in genes related to the B-cell receptor mediated maturation pathway.
Keywords: B-Lymphocytes; Cell Line, Transformed; Child, Preschool; DNA (Cytosine-5-)-Methyltransferases; DNA Methylation; Epigenesis, Genetic; Face; Female; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Immunologic Deficiency Syndromes; mutation; Primary Immunodeficiency Diseases; Sequence Analysis, DNA; Sulfites